Making the ‘Invisible’ visible: Custodial violence and the civil liberties-democratic rights movement in India - Chauhan, Preeti (International journal of law, crime and justice, 2020)
Civil Liberties and Democratic Rights Movement (henceforth CLDR movement) in India has been documenting and highlighting the issue of custodial violence for long. This paper attempts to cull out the nuances of the engagement of the civil and democratic rights movement in India with the issue of custodial violence over a period of time. The paper analyses some of the reports by the CLDR organizations, particularly, People's Union for Democratic Rights (PUDR) which are based upon the fact-findings done by these civil rights organizations. The fact-finding reports of the CLDR organizations are examined to form an understanding of the process through which the CLDR organizations approach the issue of custodial violence and the challenges therein. It also reveals the manner in which the CLDR groups foreground the voices of the people who suffered. The paper further seeks to show that the intervention of the civil and democratic rights movement on the issue of custodial violence in India made the practice of violence in custody ‘visible’ to the larger public pointing to the systematic and institutional failure of the Government to address the issue. Through its fact findings, the CLDR movement has tried to document and disseminate facts regarding torture and deaths in custody of security establishments like the police, and sexual violence in custody. In this process, the movement has also continuously jostled with the given understanding on ‘custody’ arguing for an expansion of its meaning and has sought to redefine the notion of crime, criminality and punishment.